An Economic Analysis of the Cockle Culture Industry in Thailand - Kwanming, Kulapa (1991)
This study provides a comparison of the economic performance and the socio-economic profile of cockle farmers of different farm sizes and locations in Thailand. The areas selected for the study are the northern and southern part of the Gulf of Thailand and the Andaman Sea region. Three different f arm sizes, small (1-10 rai), medium (11-50 rai) and large(over 50 rai) farms are studied. Analysis of the socio-economic profile of the cockle farmers reveals that most farmers are 30 to 50 years old, and operate their f arms as a family enterprise with their own fund. Majority of them have had only primary education,but they have very long experiences in cockle culture. Cost and return analysis indicate that cockle culture is a profit able vocation with the small farms being the most profit able. In terms of location, farms in the northern part of the Gulf of Thailand are the most profitable. The rate of return to investment of the larger farm is higher than the smaller ones. Estimation on the cost function reveals that cost economies is at farm production level of 625 mt. But the average cockle output of the sample farm is 312mt, or only 50 percent of the optimum output. Based on the findings, it is found that to increase cockle production from the small and medium size farms is possible since all of them are at present not yet operated at the minimum efficient scale of production. The production per unit area could be increased by reducing the mortality rate and utilizing more seed in cultivation. To ensure the constant supply of low cos t of cockle seed to farmers, the Government would need to enforce all necessary administrative measures to conserve the natural seed bed and to negotiate with neighbouring countries such as Malaysia for additional supply of seeds to farmers.